STRATEGI PEMBERDAYAAN UMKM MANIK-MANIK DESA PLUMBON GAMBANG MELALUI AFFILIATE MARKETING BERBASIS MARKETPLACE (UIR PRESS, 2026)
Plumbon Gambang Village has a distinctive advantage in the handicraft sector, particularly bead crafts, which are developed by Micro, Small, and Medium Enterprises (MSMEs). Some MSME actors are already familiar with marketplace applications; however, their utilization remains limited and has not yet integrated affiliate marketing strategies. This condition has led to predominantly conventional marketing practices, resulting in suboptimal sales performance. This community service activity aims to empower bead craft MSMEs in Plumbon Gambang Village to optimize digital marketing through marketplace platforms and to stimulate the improvement of the village economy. The implementation method includes socialization, training, and mentoring carried out in three stages: program socialization, training implementation, and evaluation. The Task-Based Training (TBT) approach is applied to enhance MSME actors’ understanding and skills in digital marketing, supported by a Training of Trainers (ToT) model to ensure program sustainability. The results indicate that digital marketing through marketplace platforms and affiliate marketing strategies can expand market reach and enhance digital literacy as well as the self-confidence of MSME actors. Nevertheless, challenges remain in managing online stores and adapting to digital technology. Therefore, collaboration between Village-Owned Enterprises (BUMDes) and e-commerce platforms is considered a crucial factor in promoting adaptive, inclusive, and sustainable rural economic transformation in the digital era.